The zebrafish as a model for studying neuroblastoma. Issue 1 (December 2016) - Corallo, Diana; Candiani, Simona; Ori, Michela; Aveic, Sanja; Tonini, Gian
Abstract Neuroblastoma is a tumor arising in the peripheral sympathetic nervous system and is the most common cancer in childhood. Since most of the cellular and molecular mechanisms underlying neuroblastoma onset and progression remain unknown, the generation of new in vivo models might be appropriate to better dissect the peripheral sympathetic nervous system development in both physiological and disease states. This review is focused on the use of zebrafish as a suitable and innovative model to study neuroblastoma development. Here, we briefly summarize the current knowledge about zebrafish peripheral sympathetic nervous system formation, focusing on key genes and cellular pathways that play a crucial role in the differentiation of sympathetic neurons during embryonic development. In addition, we include examples of how genetic changes known to be associated with aggressive neuroblastoma can mimic this malignancy in zebrafish. Thus, we note the value of the zebrafish model in the field of neuroblastoma research, showing how it can improve our current knowledge about genes and biological pathways that contribute to malignant transformation and progression during embryonic life.